If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 3) = 2(10 + -1x) Reorder the terms: 6(3 + x) = 2(10 + -1x) (3 * 6 + x * 6) = 2(10 + -1x) (18 + 6x) = 2(10 + -1x) 18 + 6x = (10 * 2 + -1x * 2) 18 + 6x = (20 + -2x) Solving 18 + 6x = 20 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 18 + 6x + 2x = 20 + -2x + 2x Combine like terms: 6x + 2x = 8x 18 + 8x = 20 + -2x + 2x Combine like terms: -2x + 2x = 0 18 + 8x = 20 + 0 18 + 8x = 20 Add '-18' to each side of the equation. 18 + -18 + 8x = 20 + -18 Combine like terms: 18 + -18 = 0 0 + 8x = 20 + -18 8x = 20 + -18 Combine like terms: 20 + -18 = 2 8x = 2 Divide each side by '8'. x = 0.25 Simplifying x = 0.25
| -4=2-9x | | 345= | | (x*6)+y=75 | | 11x+22=6+87 | | (x*6)+y=78 | | 3x^2-4x+9=0 | | 42k^2+36k-96=0 | | 105-5t=5 | | (4x+1)(x-3)= | | 4(4x-5)=28 | | q^2+13q+40=0 | | -x-4=-7x+8 | | 7y-15+2y=75 | | 1x+2x^2-5=4x^2-4 | | 3(2x+3)=12 | | 5x=x^2-50 | | -120+9y+80=41 | | 15n^2-80n+25=0 | | -120+9y+8c=41 | | 40=2(y-5) | | 14=y+8+y | | 4x+14=114-4 | | 10x-23=6+1 | | 2y+6-1=19 | | 9k^2+12k+4=0 | | 2(y+4)=16 | | 64x^4-80x^2y+25y^2= | | 12-2g=6 | | 102.8=g+-66.09 | | 10+9=8x+23 | | 25n^2+10n+1=0 | | 4x^2-9x+17=7x+2 |